Regulatory T Cells: Therapeutic Opportunities in Uveitis - Lee, Andrew YongJae; Foulsham, William (Frontiers in Ophthalmology, 2022)
Regulatory T cells (Tregs) are critical for the maintenance of immune tolerance and the suppression of excessive inflammation. Many inflammatory autoimmune disorders, including autoimmune uveitis, involve the loss of the suppressive capacities of Tregs. Over the past decade, Tregs’ therapeutic potential in uveitis has garnered increasing attention. Specific subsets of Tregs, including TIGIT+ and PD-1+ Tregs, have emerged as potent immunosuppressors that may be particularly well-suited to cell-based therapeutics. Studies have elucidated the interaction between Treg development and the gut microbiome as well as various intracellular signaling pathways. Numerous cell-based therapies and therapeutic molecules have been proposed and investigated using the murine experimental autoimmune uveitis (EAU) model. However, certain challenges remain to be addressed. Studies involving the use of Tregs in human patients with uveitis are lacking, and there are concerns regarding Tregs’ production and purification for practical use, their plasticity towards inflammatory phenotypes, immunogenicity, and tumorigenicity. Nevertheless, recent research has brought Tregs closer to yielding viable treatment options for uveitis.